Bradomín and the Ironies of Evil: A Reconsideration of Sonata de primavera - Sumner M. Greenfield (Studies in 20th & 21st Century Literature, 1977)
Of the four novels that form Valle-Inclán's tetralogy of seasonal Sonatas, the most problematical and dissonant is the springtime segment, which is the third in the order of composition. Valle-Inclán uncharacteristically subordinates seasonal esthetics in favor of a peculiarly ironic manipulation of the theme of conflict between good and evil set in an Italian context redolent of the Renaissance and rife with religious fanaticism. The ingrained theatricality of the young Marqués de Bradomín leads him to affect the pose of a "devilish" don Juan in order to break down the defenses of a young would-be nun who seems destined for sainthood. His juvenile posturing, however, is subverted by his immaturity and lack of self-assurance. The reinforcement of his will is brought about by the intervention of an authentic surrogate of Satan who uses him as an unwitting pawn in a confrontation with the budding saint. Evil eventually conquers Good, but the irony of his having been used is inevitably lost on Bradomín, whose perception of the world is based on himself as legend rather than on historical truth. The reaffirmation of the Sonatas as a triumph of the "poetic lie" is the primary way in which the Primavera sustains the unity of the tetralogy.
Keywords: Valle-Inclán; Sonatas; don Juan